Modern Approaches to Organizing Construction Processes in Urbanization Conditions - Zhumabek Duyshobaev (Scientific Trends, 2025)
The article examines modern approaches to the organization of construction processes in the context of urbanization, focusing on the digitalization of the construction industry. Key elements of the analysis are the introduction of building information modeling (BIM) technologies, the concept of a "smart city" and the principles of sustainable development. The impact of urbanization processes on the methods of planning, design and construction management is analyzed in order to identify key trends.
Keywords: Construction, urbanization, BIM, smart city, digitalization, Lean Construction, innovation.